KONFLIK EKOLOGIS DAN RESISTENSI BUDAYA LOKAL DALAM NOVEL MATA DI TANAH MELUS KARYA OKKY MADASARI - Nurul Islamiyah; Aswandikari; Johan Mahyudi; Ahmad Sirulhaq; Saharudin (Universitas Hamzanwadi, 2026)
Issues of environmental degradation and the marginalization of local cultures have become increasingly prominent in contemporary Indonesian literature as a response to the exploitation of natural resources and the penetration of modernity that threaten the sustainability of indigenous communities. Okky Madasari’s novel Mata di Tanah Melus strongly represents the complex relationship between humans, nature, and the culture of the Melus community in Belu, East Nusa Tenggara, within the context of ecological conflict. This study aims to describe the forms of ecological conflict and local cultural resistance represented in the novel by applying Greg Garrard’s ecocriticism framework, particularly the concepts of wilderness, apocalypse, dwelling, and pastoral. The research employs a descriptive qualitative method using content analysis of the novel. The findings reveal that ecological conflict is portrayed through forest destruction, disputes over ancestral land, the exploitation of Mount Lakaan, and violence against nonhuman beings, reflecting both ecological and cultural crises. Meanwhile, local cultural resistance is manifested in harmonious living practices with nature, the preservation of traditional rituals, respect for sacred landscapes and animals, and efforts to defend living space from capitalist expansion. These findings affirm that the novel not only presents a narrative of ecological conflict but also offers a critique of modern anthropocentric paradigms and positions local wisdom as a foundation for sustainable ecological ethics.